Social Support Modulates Stress-Related Gene Expression in Various Brain Regions of Piglets - Kanitz, Ellen; Hameister, Theresa; Tuchscherer, Armin; Tuchscherer, Margret; Puppe, Birger (Frontiers in Behavioral Neuroscience, 2016)
The presence of an affiliative conspecific may alleviate an individual's stress response in threatening conditions. However, the mechanisms and neural circuitry underlying the process of social buffering have not yet been elucidated. Using the domestic pig as an animal model, we examined the effect of a 4-h maternal and littermate deprivation on stress hormones and on mRNA expression of the glucocorticoid receptor (GR), mineralocorticoid receptor (MR), 11ß-hydroxysteroid dehydrogenase (11ß-HSD) types 1 and 2 and the immediate early gene c-fos in various brain regions of 7-, 21- and 35-day old piglets. The deprivation occurred either alone or with a familiar or unfamiliar age-matched piglet. Compared to piglets deprived alone, the presence of a conspecific animal significantly reduced free plasma cortisol concentrations and altered the MR/GR balance and 11ß-HSD2 and c-fos mRNA expression in the prefrontal cortex (PFC), amygdala and hypothalamus, but not in the hippocampus. The alterations in brain mRNA expression were particularly found in 21- or 35-day old piglets, which may reflect the species-specific postnatal ontogeny of the investigated brain regions. The buffering effects of social support were most pronounced in the amygdala, indicating its significance both for the assessment of social conspecifics as biologically relevant stimuli and for the processing of emotional states. In conclusion, the present findings provide further evidence for the importance of the cortico-limbic network underlying the abilities of individuals to cope with social stress and strongly emphasize the benefits of social partners in livestock with respect to positive welfare and health.